UPAYA MENINGKATKAN HASIL BELAJAR SISWA TERHADAP PASSING BAWAH BOLA VOLI MELALUI METODE VARIASI - Syaifullah Syaifullah; Juhanis Juhanis (Jurusan Pendidikan Teknik Elektro, 2024)
This study aims to describe planning, action, observation, reflection, through the variation method of lower passing in volleyball learning for class V.B UPT SPF SDN Rappocini students. This research was carried out for 3 meetings each in cycle I and cycle II, which are designed by this research is the basic ability of lower passing as psychomotor data and the value of exercise questions as a value of knowledge (cognitive). Observation as attitude data (affective). The data source of this research is class V.B UPT SPF SDN Rappocini students totaling 36 students. Collecting data on lower passing learning outcomes using a fill-in assessment sheet in cycle I and cycle II, the data collected was analyzed quantitatively. The results of quantitative analysis of volleyball lower passing learning outcomes data show that the number of students who completed the first cycle was 26 people with a percentage of 69.44%, while the number of students who completed the second cycle was 33 people with a percentage of 91.67%. The results of this study indicate that learning physical education through variation methods can improve the learning outcomes of class V.B students on the lower pass in the Volleyball game at UPT SPF SDN Rappocini.